2014
DOI: 10.1016/j.egypro.2014.11.629
|View full text |Cite
|
Sign up to set email alerts
|

Assessing CO2 Adsorption Capacities onto Shales Through Gravimetric Experiments: A First Step in the Feasibility Study of Coupling “Fracking” with Carbon Storage

Abstract: Oil and gas production from shale formations stimulated by hydraulic fracturing (or "fracking") is an abundant source of domestically available energy for the United States of America. Today, shale formations are mostly fracked using fresh water or brine which induces large volumes of water to manage. The use of CO 2 is an alternative fracking option and appears to have several benefits, as (1) it does not require water but carbon dioxide; as (2) injection of carbon dioxide could enhance the gas recovery; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…They also showed that the helium compressibility can be obtained using correlation to measure the void space, whereas the CO 2 values should be obtained using other methods. Lafortune [20] measured CO 2 adsorption on Mesozoic Marine Basin shale samples from France using magnetic suspension balance. The samples were crushed to powder size, and used for the adsorption experiments.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that the helium compressibility can be obtained using correlation to measure the void space, whereas the CO 2 values should be obtained using other methods. Lafortune [20] measured CO 2 adsorption on Mesozoic Marine Basin shale samples from France using magnetic suspension balance. The samples were crushed to powder size, and used for the adsorption experiments.…”
Section: Introductionmentioning
confidence: 99%